Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: 1. Agricultural cooperatives as a mechanism to strengthen the solidarity and social economy and achieve territorial development in the Tafrata Plain in northeastern Morocco Dr. Smail Bouguelba ,Dr. El-Kallouchi Mohamed 2. Analysis of Annual and Monthly Temperature Fluctuations in Makkah for the Period 1950–2023 Ms. Njoud Abd Alaziz Alamro ,Prof. Hussein Ahmed Almohamad 3. The Role of Non-Governmental Organizations in Achieving Sustainable Social Development In light of Vision 2030 : A Survey study of Workers in the Social Development Committees in Taif Governorate Mr. Ali Jamaan sahlan Alghamdi 4. Sustainable development discourse on the environmental crisis in an unequal world A Socio-critical reading Dr. Aida Elhadi Ben Kraiem 5. The legal purposes and their impact on protecting the Muslim from deviation Mr. Housin Mohammed Agha 6. Books of classes and translations among the Arabs from The Second Century AH - Fourteenth Century AH Dr. Maha Mohammed Alqahtani 7. Spatial analysis of the distribution of banks and commercial banks in Hail, a study using geographic information systems (GIS) Ms. Maryam Radhi Sayah Alshamri